1988
DOI: 10.1084/jem.167.2.440
|View full text |Cite
|
Sign up to set email alerts
|

Oral vaccination. Identification of classes of proteins that provoke an immune response upon oral feeding.

Abstract: Oral immunization of an animal is generally hard to achieve unless large quantities of antigen are administered. In this study a number of antigens were tested for their ability to elicit a systemic immune response upon oral administration. It was found that bacterial pili, LTB, lectins, and a viral hemagglutinin were all able to elicit significant antibody titers upon oral feeding. The immune response thus generated to LTB and K99 pili could be completely abolished by cofeeding a number of sugars that have cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(79 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…Indeed, some studies have shown that the oral administration of antigens capable of binding to mucosal surface induces strong immune responses. 36 In fact, Tat has been reported to bind to heparan sulfate proteoglycans present in the extracellular matrix and on the cell membranes 37,38 as well as to integrins present on the cellular surface of professional antigen presenting cells. 39 However, some issues still need to be solved in the field of mucosal vaccines.…”
mentioning
confidence: 99%
“…Indeed, some studies have shown that the oral administration of antigens capable of binding to mucosal surface induces strong immune responses. 36 In fact, Tat has been reported to bind to heparan sulfate proteoglycans present in the extracellular matrix and on the cell membranes 37,38 as well as to integrins present on the cellular surface of professional antigen presenting cells. 39 However, some issues still need to be solved in the field of mucosal vaccines.…”
mentioning
confidence: 99%
“…These molecules possess a modular organization with at least one noncatalytic domain that reversibly binds to a specific mono-or oligosaccharide (47,48). For example, the most powerful mucosal antigens/adjuvants identified to date, cholera toxin (CT) secreted by Vibrio cholerae and Escherichia coli heat-labile enterotoxin (LT), feature a lectin-like structure with five modules (B subunit) that bind to oligosaccharide residues on membrane receptors (1,46). In keeping with this view, it has recently been reported that plant lectins, also showing a modular structure, such as mistletoe and Lycospersicum esculentum lectins, are potent mucosal immunogens and enhance the immune response to coadministered antigens (25,50).…”
mentioning
confidence: 99%
“…Indeed, the experiments carried out with recombinant viral particles also did not mention specific IgE synthesis (1,11). Furthermore, previous studies using oral immunizations have reported sensitization of IgE suppressor cells (29) with concomitant suppression of serum IgE response due to tolerance induced by oral feeding with proteins (37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the immunogenicity of the CPSMV capsid proteins could be attributed to their "lectin-like" binding activities, which are comparable to similar activities found in bacterial pili, lectins, cholera labile toxin B subunit, and viral hemagglutinin. These are all known to bind to the glycolipids or glycoproteins of the intestinal mucosa cells, thus stimulating these cells to transport the antigen into the systemic circulation (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%